Persuasive Communication in Selling Sharia-based Product in Indonesia During Covid-19: A Cognitive Dissonance Perspective - Andi Tirta Kurniawan; Oktaviana Purnamasari (Universiti Sains Islam Malaysia, 2024)
AL-I’LAM –Journal of Contemporary Islamic Communication & Media, 4(1), 75–85